Tea cafés and the Hong Kong identity: Food culture and hybridity. (November 2019) - Chan, Selina Ching
This article examines the meanings of caa caan teng (茶餐廳, local cafés) in Hong Kong and the implications of such cafés on the Hong Kong identity. It argues that the local café is a representation of Hong Kong culture because it reflects Hong Kong's political, economic, and social developmental paths and mirrors the everyday life of its people. I investigate how the interaction of different immigrant cultures in Hong Kong has resulted in the invention of hybrid foods at the local café. These foods demonstrate hybridity as the transgression of boundaries through the negotiation of cultural differences among migrants, as well as those between migrants and colonialists. I argue that hybridity in local cafés reflects the power relations among the locals in Hong Kong, between locals and colonialists, and between locals and the new authorities in Beijing. Hybridity found in local cafés symbolizes the Hong Kong identity, as an entanglement between the multiplicity of Chinese ethnicities and the colonial modernity as characterized by flexibility, efficiency, choice, and diversity. These features differentiate the Hong Kong people from the colonialists and the mainlanders, thus constructing their identity and subjectivity, as former colonial subjects now living in the 'periphery' of the motherland.